Using the GIS in studying and preparing the thematic maps for the coverage of water and sanitation networks and solid waste management during the crisis in Homs governorate (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The crisis in Syria heavily impacted public infrastructure as well as the provision of basic services. This strongly affected the population in all Syrian governorates since the beginning of the crisis seven years ago. The water sector is considered one of the most affected. Hostilities led to damages in the networks and ensuing water cuts. In addition, main pumping stations, boreholes and sanitation networks ceased to function. This research aims at identifying the locations and extent of damages in the water networks in Homs governorate based on the percentage of water and sanitation networks as well as solid waste management services compared to the pre-conflict situation. The research depends on utilizing the Geographic Information Systems (GIS) based on descriptive data. The information used comprises primary data collected in the field using structured questionnaires filled by the local population as well as secondary data produced by humanitarian organizations, SARC and governmental institutions. The results show decreased the coverage of water and sanitation networks in Homs Governorate notably outside the county centers while it is almost non-existent in the urban areas. The latter include the southern and eastern counties Al Qariateen, Sadd, Mheen, Al furqulus, Al Ruqama and Hisia. Furthermore, more than half of the population living in the eastern urban areas rely on water trucking. The discontinuity of municipal services and malfunction of solid waste removal trucks resulted in the accumulation of waste in many areas. Therefore, the state of solid waste management is evaluated to be mostly “bad”, while the reminder only reaches “medium” category, which means, the municipalities do not collect the waste, or collect and dump inside the city. This situation strongly increases the risk of an outbreak of infectious diseases.